A randomised double-blind, multicentre parallel group study to compare the tolerability and efficacy of moclobemide administered in three different dosage regimens in depressed outpatients in psychiatric practice - Dr Vukovic, Karen Margaret-Ann (My University, 1995)
Moclobemide is a reversible monoamine oxidase inhibitor. It is a short acting antidepressant, and previously studies were done comparing 300 to 600 mg dosages administered three times daily. Data on a twice daily dosage schedule is limited. This study compares the efficacy and tolerability of Moclobemide 150 mg twice daily as compared to two different three times a day schedules with total daily dosages of 300 to 450 mg respectively. Thirty one adult outpatients with major depressive disorder (as defined by DSM-IIIR) were included in this trial. It was controlled in a randomised double-blind manner. All treatments were found to be effective and no clinically significant differences between treatments could be demonstrated in this respect. Group 3 (150 mg b.d.) was found to be slightly more effective than the other two groups. Moclobemide was found to be effective at all dosage regimens with respect to treating co-morbid symptoms of anxiety and agitation. There were no differences between the groups with respect to type and frequency of adverse events. Overall tolerability was found to be good in all the treatment groups. Since the twice daily dosage is more convenient, it has been suggested that compliance will be enhanced on this regimen. The treatment response rates obtained confirm this conclusion.
A dissertation submitted to Faculty of Medicine in part fulfilment of the required for the degree of Master of Medicine in Psychiatry at the University of the Witwatersrand
Keywords: Moclobemide; Depression; Metabolism